Pgv and progressive iptu as an instrument of urban reform: innovation challenges in the city of Araraquara-SP - Falcoski, Luiz Antonio Nigro; Paiva, Claudio Cesar [UNESP]; Pierini, Claudio Robert; Menzori, Ivan Damasco (Univ Estado Rio Janeiro, 2023)
Araraquara, a city in the state of Sao Paulo in Brazil has suffered a strong real estate speculative process, indiscriminate territorial expansion and socio-spatial segregation promoted by patrimonial social agents. This process is in line with traditional taxation and the lack of institutional commitment to the social function of land and other urban planning instruments. To correct distortions arising from the misappropriation of land valuation, a Generic Value Plant (PGV) is established through the Urban Property and Land Tax (IPTU). The objective is to evaluate and spatialize data from PGV/2017 (LC No. 882/2017), pointing out limits and instrumental problems. The method consisted of surveying real estate values in the PGV/2017 and producing a geoprocessed strategic map, based on the values per faces of urban blocks for analysis and identification of distortions, limitations and excesses allowed by law. As a result, the needs for reassessment of the PGV/2017 and the inclusion of new spatial instruments stand out. Finally, the mapping produced points to the limits of the traditional mechanisms of urban and tax policy, which should not be reduced to fiscal aspects alone. This work signals the need for instrumental and methodological modernization of urban and tax policy, with social innovation, normative integration, new territorial pacts on the social function of property, as well as new governance in the production of the city.
Keywords: Tax Instruments; Planning Instruments; Urban Policy; Tax Policy; Urban Governance